Influence of Organizational Culture, Work Environment, and Work Motivation on Employee Performance - Mochamad Albert Nurcahyo; Rhian Indradewa (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Employee performance is one of the benchmarks for government agencies in creating more value to produce a product or service to achieve organizational goals, one of the factors that affect employee performance is the motivation factor motivation can be influenced by a good work environment and organizational culture. Good organizational culture and a conducive work environment will have an impact on the emergence of motivation for employees which in turn will have an impact on improving employee performance. This study aims to analyze the influence of organizational culture, work environment, and work motivation on employee performance. This study uses a survey method by distributing questionnaires to employees of the Education Financing Service Center Kemdikbudristek as respondents. This study uses quantitative research methods, and analytical methods using Structural Equation Modeling (SEM) with Smart PLS applications. Respondents in this study were 85 people. The results of this study indicate that all indicators used in this study are valid and reliable. The conclusions of this study: organizational culture variables affect work motivation, organizational culture variables affect employee performance, and the work environment affects employee performance, but the work environment variable does not affect work motivation and work motivation does not affect employee performance.